2015
DOI: 10.1371/journal.pone.0119810
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Platelet Glycoprotein Receptor Ib and IIb/IIIa Expression in Patients with Acute and Chronic Cerebrovascular Disease

Abstract: BackgroundAnimal models have been instrumental in defining thrombus formation, including the role of platelet surface glycoprotein (GP) receptors, in acute ischemic stroke (AIS). However, the involvement of GP receptors in human ischemic stroke pathophysiology and their utility as biomarkers for ischemic stroke risk and severity requires elucidation.AimsTo determine whether platelet GPIb and GPIIb/IIIa receptors are differentially expressed in patients with AIS and chronic cerebrovascular disease (CCD) compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…При гетерозиготном варианте С/Т экспрессия рецепторов GpIb/IX/V на тромбоцитах не так сильно выражена, однако в некоторых исследованиях выяв-лен повышенный риск тромбообразования у носителей этого варианта гена [16]. В ряде исследований показано, что носители аллеля С имеют повышенный риск коронарного тромбоза, ишемического инсульта и снижения возраста его наступления [17].…”
Section: Discussionunclassified
“…При гетерозиготном варианте С/Т экспрессия рецепторов GpIb/IX/V на тромбоцитах не так сильно выражена, однако в некоторых исследованиях выяв-лен повышенный риск тромбообразования у носителей этого варианта гена [16]. В ряде исследований показано, что носители аллеля С имеют повышенный риск коронарного тромбоза, ишемического инсульта и снижения возраста его наступления [17].…”
Section: Discussionunclassified
“…Two techniques are available to study the CD41/CD61 complex, GPIIb-IIIa, at levels less than 5% of normal. This level is between 5 and 15% for type II, whereas type III is only a qualitative deficiency with variable levels of the surface integrin (Kraft, Drechsler, Gunreben, Heuschmann, & Kleinschnitz, 2015;Wagner et al, 1996).…”
Section: Analysis Of Platelets In Fcmmentioning
confidence: 98%
“…A study in Chinese population was performed by Zhang et al who analyzed the above-mentioned polymorphism and observed that the frequency of D allele of VNTR was considerably higher in patients than in controls (Table 3) [28]. In contrary to these positive results, there are also a number of studies which show no association between afore mentioned GP1BB polymorphisms and ischemic stroke (Table 4) [18,61,66].…”
Section: -Kd Beta Chain (Gpibβ)mentioning
confidence: 99%
“…Even though several positive studies exist, there is also a number of minor controversies concerning the functional role of rs5918 in different populations, which do not support any association between rs5918 polymorphism and ischemic stroke [9,28,32,44,45,[60][61][62][63]. In an initially performed meta-analysis, which included 26 studies with five referring to rs5918 polymorphism, a dominant genetic model revealed no linkage with ischemic stroke [49].…”
Section: Gpiib/iiia -Itga2b and Itgb3 Genesmentioning
confidence: 99%